Studies in Zechariah - Gaebelein, Arno Clemens, 1861-1945 (Salt Lake City, UT : Project Gutenberg, 2011)
"Studies in Zechariah" by Arno Clemens Gaebelein is a theological exposition written in the early 20th century. The work focuses on the prophetic visions and messages attributed to the biblical prophet Zechariah, exploring their implications for both the historical Jewish context and their relevance to eschatological themes in contemporary times. The opening of the book includes a foreword where Gaebelein reflects on the evolution of his understanding of the prophecies over the years, indicating a growth in his interpretations since the book's initial publication. He introduces Zechariah, describing his significance as both a priest and a prophet, and details his mission to encourage the Jewish people during their struggle to rebuild the Temple after their return from Babylon. As the text progresses, it sets the scene for the prophet's visions, emphasizing the divine encouragement offered to a disheartened community and hinting at the greater promises of restoration and mercy that will unfold in the following chapters. The initial address to the people serves as both an urgent call for repentance and a promise of God's eventual return to Jerusalem, laying the foundation for the subsequent prophetic revelations. (This is an automatically generated summary.)
Release date is 2011-05-24
Produced by Keith G. Richardson
Keywords: Bible. Zechariah -- Commentaries